Prevalence, patterns of multimorbidity, and its correlations with health-related quality of life in rural southwest China: a cross-sectional study - Xie, Na; Xiong, Huali; Jiang, Xin (Frontiers in Medicine, 2025)
BackgroundThe prevalence, patterns, and impact of multimorbidity on health-related quality of life (HRQoL) remain inadequately understood among rural populations in southwest China. This study seeks to fill this knowledge gap by systematically examining these aspects.MethodsParticipants were recruited from the China Multi-Ethnic Cohort (CMEC) study. Incident cases of 13 chronic conditions were documented. Multimorbidity was defined as the presence of two or more chronic conditions in an individual. Principal component factor analysis (PCFA) was performed to identify patterns of multimorbidity. Tobit regression analysis and restricted cubic spline were employed to assess the correlation between multimorbidity patterns and HRQoL.ResultsA total of 2,998 participants were enrolled, with a mean age of 50.65 years (SD = 11.99). The prevalence of multimorbidity was 48.50%. Four multimorbidity patterns were identified by PCFA: circulatory system pattern, digestive system pattern, metabolic syndrome pattern, and hepatobiliary system pattern. All four patterns were negatively correlated with HRQoL, as demonstrated by tobit regression analysis (β = −0.024, β = −0.020, β = −0.007, β = −0.018; all p < 0.001). Restricted cubic spline also demonstrated the negative correlation between different multimorbidity patterns and HRQoL, after adjusting for potential confounding factors. Subgroup analysis in different gender, age, and average yearly family total income also demonstrated these negative correlations.ConclusionThe prevalence of multimorbidity is relatively high in rural southwest China. Distinct multimorbidity patterns were correlated with poorer HRQoL. These findings enhance the understanding of multimorbidity patterns and may inform the development of tailored primary healthcare services.